Nonlinear evolution equations and applications - Jäger, Willi; Lorenz, Thomas; Tambulea, Adela (Reactive flows, diffusion and transport, 2007)
Mathematical analysis provides several powerful tools for describing dynamic processes in science and economics. Here the role of ordinary and partial differential equations within the SFB 359 is briefly sketched. Then two examples are presented in more detail: Firstly, the analytical description of gradostat demonstrates how sensitively a system of ODEs might depend on its parameters. Secondly, shape evolutions show how the tools of set-valued analysis provide an alternative to level-set methods. The key aim here is to extend evolution equations beyond vector spaces.